Echoes of the Tragic in the Sacred Landscape of Ancient Salamis: A Geospatial Analysis of Hero Cult - Delacruz, Michael (Journal of Greek Archaeology, 2021)
What follows is a geospatial analysis of the sacred landscape of Ancient Salamis, an island polity located in the Saronic Gulf, which has been traditionally identified as the seat of the House of Telamon, from where Ajax the Greater (Αἴας ὁ Τελαμώνιος) reputedly launched his expedition to support the campaign against Troy (Iliad. 2.557). In particular, this analysis focuses on the relationship between two sanctuaries purported to be dedicated to Ajax and possibly coexisting during the late Classical and early Hellenistic periods (Figure 1): the first, the principal Temple of Ajax (ναὸς Αἴαντος) reported by Pausanias (Hell. Per. 1.35.3) to have been located at the Classical-period town at the Bay of Ampelakia; and the second, situated at a rural location some 12km away amidst the remains of a Mycenaean citadel at Kanakia and neighboring cult precinct at Pyrgiakoni at the far western side of the island excavated and identified by Yannos Lolos in 2005 (Lolos 2012: 47ff). Strong archaeological evidence suggests that this rural location (Figure 2) was the site of chthonic votive practice (ibid.: 49) often associated with hero or ancestor cult during the later Classical and Hellenistic periods and during a time when Athenian affiliation with the island and the figure of Ajax was officially sanctioned as a consequence of the political re-engineering of the Athenian polis under Kleisthenes.